A performance enhancement of physical layer at Wi-MAX system with RLDPC code - Sandeep Bawage; Manjula S; A. M. Bhavikatti (Institute of Advanced Engineering and Science, 2021)
In present wireless communication network, the error correction codes plays the major role for efficient data transmission in noisy environments. To get minimum BER and PAPR has been the main aim towards the field in forward error control coding. Majority of the researchers has considered turbo codes at specific SNR over AWGN channel but have complexity issues with the iterative output decoder and causes degradation in the Wi-Max network system. In this paper, the author presents and evaluates WiMAX physical layer performance with using MIMO technologies, where a Robust-LDPC technique of coding and decoding in OFDM based WiMAX system is consider. The decoding method of RLDPC has processed by Belief Propagation at the logarithmic domain in an iterative manner, the proposed methodology shows good decoding outcome for RLDPC codes at Rician and Rayleigh channel. Moreover, the applicability of our proposed model channel codes is defined under IEEE Wi-MAX standard and the results analysis is done under different code-rate and modulation schemes.